A microCT Study of Three-Dimensional Patterns of Biomineralization in Pig Molars - Sova, Susanna S.; Tjäderhane, Leo; Heikkilä, Pasi A.; Jernvall, Jukka (Frontiers in Physiology, 2018)
Domestic pig molars provide an interesting system to study the biomineralization process. The large size, thick enamel and complex crown morphology make pig molars relatively similar to human molars. However, compared to human molars, pig molars develop considerably faster. Here we use microCT to image the developing pig molars and to decipher spatial patterns of biomineralization. We used mineral grains to calibrate individual microCT-scans, which allowed an accurate measure of the electron density of the developing molars. The microCT results show that unerupted molars that are morphologically at the same stage of development, can be at markedly different stage of enamel biomineralization. Erupted molars show increased electron density, suggesting that mineralization continues in oral cavity. Yet, our comparisons show that human enamel has slightly higher electron density than pig enamel. These results support the relatively low hardness values and calcium level values that have been reported earlier in literature for pig teeth. The mineral calibration was an efficient method for the microCT-absorption models, allowing a relatively robust way to detect scanning artifacts. In conclusions, whereas thin sections remain the preferred way to analyze enamel features, such as incremental lines and crystal orientation, the microCT allows efficient and non-destructive comparisons between different teeth and species.